Perceptions regarding teaching and learning in research at a higher education institution: towards the improvement of research capabilities - Rodríguez, Melissa (2021)
The purpose of this study was to analyze the perception of students, teachers, and authorities in relation to teaching and learning in the research courses of the Pedagogy and Education Sciences Program at the Universidad Nacional Autónoma de Honduras (UNAH for Spanish acronym), On campus modality at Ciudad Universitaria and UNAH-Valle de Sula, on the first academic term of 2017. The approach of the research was qualitative; the target population was constituted by both, the students enrolled in the research workshop and the teachers who offered research courses. The research presents a Convenience sampling, based on selective criteria, focus groups and semi-structured interviews were applied to the teachers. In conclusion, weaknesses were found in the pedagogical practices and the need of teachers’ collective consideration was observed, consequently, in 2019, the “First Gathering of Teachers for the Education Research” took place, establishing agreements and guidelines for a Pedagogy of research.